(untitled) (American Journal of Business Management, Economics and Banking, 2024)
While the concept of a green economy holds significant promise for addressing environmental and social challenges, it also faces several problems and obstacles in today’s world. Addressing these problems requires a concerted effort from governments, businesses, and civil society. While challenges exist, the transition to a green economy remains crucial for mitigating environmental crises and ensuring long-term prosperity. The article discusses about the problems and also developing and implementing effective policies, fostering innovation, ensuring equitable transitions, and educating the public about the importance of sustainability.